DISCOURSES ON THE CONCEPT OF THE MONUMENT “UNITED FOR LATVIA” IN LATGALIAN PRESS (THE 1920S AND 1930S) - Malahovskis, Vladislavs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The monument “United for Latvia”, unveiled in the centre of Rezekne in 1939, is dedicated to the participants of the Latvian War of Independence (1918–1920. ), who took part in the liberation of Latgale from the Bolsheviks. In a broader sense, it symbolizes the whole Latgale, the liberation of the people from foreign powers, as well as the unity of Latgale with the rest of Latvia. Nowadays, the monument is a signature of Latgale, its image is widely used in booklets, souvenirs, on the covers of books and brochures, in advertisements, etc. Despite the significance and popularity of the monument, its history has been little studied. Before the monument was erected, there was a series of discourses on its concept in Latgalian press. The aim of the article is to identify in the course of the exploration of Latgalian press publications the direction of the public opinion in the 1920s and 1930s on the discourses of what should be the ideological and visual appearance of the monument of the liberation of Latgale and its unification with the rest of Latvia. The study is based on the historical approach to discourse and qualitative, comparative analysis of information. The study examines two topics of discourse: the choice of the monument site and the type of the monument; the ideological and visual solution of the monument.